Industrial activated sludge exhibit unique bacterial community composition at high taxonomic ranks - Ibarbalz, Federico Matias (2013)
Biological degradation of domestic and industrial wastewater by activated sludge depends on a common process of separation of the diverse self-assembled and self-sustained microbial flocs from the treated wastewater. Previous surveys of bacterial communities indicated the presence of a common core of bacterial phyla in municipal activated sludge, an observation consistent with the concept of ecological coherence of high taxonomic ranks. The aim of this work was to test whether this critical feature brings about a common pattern of abundance distribution of high bacterial taxa in industrial and domestic activated sludge, and to relate the bacterial community structure of industrial activated sludge with relevant operational parameters. We have applied 454 pyrosequencing of 16S rRNA genes to evaluate bacterial communities in full-scale biological wastewater treatment plants sampled at different times, including seven systems treating wastewater from different industries and one plant that treats domestic wastewater, and compared our datasets with the data from municipal wastewater treatment plants obtained by three different laboratories. We observed that each industrial activated sludge system exhibited a unique bacterial community composition, which is clearly distinct from the common profile of bacterial phyla or classes observed in municipal plants. The influence of process parameters on the bacterial community structure was evaluated using constrained analysis of principal coordinates (CAP). Part of the differences in the bacterial community structure between industrial wastewater treatment systems were explained by dissolved oxygen and pH. Despite the ecological relevance of floc formation for the assembly of bacterial communities in activated sludge, the wastewater characteristics are likely to be the major determinant that drives bacterial composition at high taxonomic ranks.